2013
DOI: 10.1016/s0254-6272(13)60100-4
|View full text |Cite
|
Sign up to set email alerts
|

Short and long-term efficacy of combining Fuzhengliqi mixture with acupuncture in treatment of functional constipation

Abstract: Both FLM and acupuncture can significantly shorten the defecation interval and GITT, increase MTL levels in serum, decrease the scores of stool property, constipation symptoms, and accompanying symptoms in patients with FC to increase their life quality. The combined therapy is much better in long-term efficacy and the safety is also good, worth spreading in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 8 publications
1
44
0
1
Order By: Relevance
“…In the current study, both acupoint at ST36 and tibial nerve were chosen for TN. It was reported that EA increased the frequency of defecation [ 25 ] and decreased stool property, constipation symptom grade, and accompanying symptom grade [ 26 – 28 ], which was consistent with the results of our study. In previous studies, ST36 was also applied to treat constipation by combining it with other acupoints or moxibustion and was shown to be effective [ 13 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, both acupoint at ST36 and tibial nerve were chosen for TN. It was reported that EA increased the frequency of defecation [ 25 ] and decreased stool property, constipation symptom grade, and accompanying symptom grade [ 26 – 28 ], which was consistent with the results of our study. In previous studies, ST36 was also applied to treat constipation by combining it with other acupoints or moxibustion and was shown to be effective [ 13 ].…”
Section: Discussionsupporting
confidence: 93%
“…There were 6 high quality trials [ 14 , 16 , 17 , 23 , 24 , 27 ] which could be assessed as 5 according to Jadad scoring system [ 31 ], but sample sizes of them were all small. A trial containing 553 samples was evaluated to have a Jadad score of less than 3 due to the flaw in design [ 15 ].…”
Section: Acupuncturementioning
confidence: 99%
“…The control groups in the literature included medications, other methods of stimulation, and acupuncture plus medications. Medications used in the control group included conventional medicine [ 15 , 16 , 23 , 24 ] (Mosapride, Macrogol 4000, Lactulose) and Chinese herbal medicine [ 15 , 22 ] (Fuzhengliqi mixture and Plantain and Senna Granule). Sham acupuncture [ 17 , 27 , 29 ], shallow acupuncture [ 16 , 23 , 24 ], regular electrical stimulation [ 19 ], and other methods of stimulation were performed as control methods.…”
Section: Acupuncturementioning
confidence: 99%
See 2 more Smart Citations